Comparing the potential of different strategies for colour tuning in thin film photovoltaic technologies. Issue 1 (31st December 2018) - Pascual-San José, Enrique; Sánchez-Díaz, Antonio; Stella, Marco; Martínez-Ferrero, Eugenia; Alonso, Maria Isabel; Campoy-Quiles, Mariano
ABSTRACT: While the performance of some emerging solar cell technologies is rocketing, there are other important parameters that also need to be considered for industrialization, including aesthetics, payback time or long-term stability. More specifically, aesthetical features of the solar cells play a very important role in the path towards the integration of these semi-transparent technologies into the buildings and windows of the future. In this work, we have implemented a theoretical methodology to study in depth colour tuning in polymer-based organic photovoltaic cells that uses experimentally complex refractive indices. We compare quantitatively basic interference effects (through active layer thickness), binaries with different donors and different acceptors, and ternary systems where the third component is either active or a simple dye. For hybrid perovskite solar cells, we compare the colour tuning capability of blending and alloying. Additionally, we show that the same theoretical framework can be employed for the so-called inverse problem, i.e. determining the best solar cell parameters (specific materials, donor:acceptor ratio and photoactive film thickness) that can reproduce a desired set of chromaticity coordinates. Graphical Abstract: